Penerapan Teknologi QR Code untuk Meningkatkan Efisiensi Absensi Karyawan Berbasis Android - Kastella, Thufail Bintang; Ujianto, Erik Iman Heri (TIN: Terapan Informatika Nusantara, 2025)
PT. Harta Samudera Ambon faces several challenges in managing employee attendance due to the continued use of manual methods such as signatures and paper-based records. This conventional system creates a number of issues, including a high potential for proxy attendance, frequent recording errors, delayed data recap, and the inability to monitor employee presence accurately and in real time. These shortcomings negatively impact the effectiveness of administrative operations and the reliability of attendance data required for performance evaluation. To address these problems, this study develops an Android-based attendance system using QR Code technology, which enables automatic, accurate, and instant recording through a scanning mechanism. The system also incorporates additional features such as employee data management, work schedule configuration, attendance history tracking, and digital leave submission. The research methodology consists of requirement analysis, system architecture design, application implementation, and system evaluation using Black Box Testing to validate functional performance. The results indicate that the system significantly improves the speed of the attendance process, reduces recording errors by more than 85%, and eliminates the possibility of proxy attendance. Furthermore, the integrated admin dashboard simplifies centralized monitoring and management of attendance data. Despite these positive outcomes, the system still relies on internet connectivity and lacks advanced security features. Future enhancements may include GPS integration, dynamic QR Code encryption, and automated analytics reporting.